Digitalization of cultural industries: Evidence from the official Spider-Man movie TikTok account - Hernando Velasco, Alicia; Matsumoto, Mitsuko; Dominguez-Santos, Susana; Lacasa, Pilar (Convergence: The International Journal of Research into New Media Technologies, 2024)
The digitalization of culture and creative industries has presented both challenges and opportunities. To effectively engage audiences and ensure their constant interest, these industries must continually adapt their circulation strategies. The objectives of this study are threefold: 1) analyze the strategies employed by the Marvel Cinematic Universe (MCU) to engage with the fan community; 2) examine the interplay between fiction and reality based on the relationships between characters and actors, as shown in social network posts; and 3) determine how the discourse in the film ‘Spider-Man: No Way Home’ is reconstructed on TikTok, leveraging its particular ‘affordances’ (Gibson, 1979). A mixed methodology approach was utilized, combining the use of Analisa.io software to provide a comprehensive view of the Spider-Man official account’s activities and user engagement with a detailed analysis of the thematic, multimodal, and discursive aspects of TikTok videos published by the account. The findings reveal that the MCU employs TikTok as a marketing tool for the new movie, utilizing three main strategies that align with the characteristics of transmedia storytelling and enhanced audience engagement: 1) strategic selection of publication moments for the growth of follower engagement; 2) extensive use of teasers; and 3) leveraging the presence of actors as a key element to facilitate fan identification.
Keywords: cultural industries; Marvel; TikTok; platform studies; affordances; multimodal discourse analysis; mix methods